Eliminating the Neglected Tropical Diseases: Translational Science and New Technologies. - Peter J Hotez; Bernard Pecoul; Suman Rijal; Catharina Boehme; Serap Aksoy; Mwelecele Malecela; Roberto Tapia-Conyer; John C Reeder (Public Library of Science (PLoS), 2016)
Today, the World Health Organization recognizes 17 major parasitic and related infections as the neglected tropical diseases (NTDs). Despite recent gains in the understanding of the nature and prevalence of NTDs, as well as successes in recent scaled-up preventive chemotherapy strategies and other health interventions, the NTDs continue to rank among the world's greatest global health problems. For virtually all of the NTDs (including those slated for elimination under the auspices of a 2012 London Declaration for NTDs and a 2013 World Health Assembly resolution [WHA 66.12]), additional control mechanisms and tools are needed, including new NTD drugs, vaccines, diagnostics, and vector control agents and strategies. Elimination will not be possible without these new tools. Here we summarize some of the key challenges in translational science to develop and introduce these new technologies in order to ensure success in global NTD elimination efforts.